Eco-ethologicol characterisation of alien species: Vinous-throated Parrotbill, Paradoxornis webbianus, and Ashy-throated Parrotbill, Paradoxornis alphonsianus, with radiotracking - Luoni, Federica; Gagliardi, Alessandra; Tosi, Guido (Rivista Italiana di Ornitologia, 2012)
The study of the Parrotbill in Province of Varese during spring and autumn 2006 is based on 7 birds marked with radio-tags of 0.43 g. The dimension of home range during the breeding season is significantly smaller than in autumn (7 ha). The analysis of vegetation in the home range showed a preference for wetland and swamp bush by these birds.